The Association of Duffy Binding Protein II Polymorphisms and its Antigenicity in Plasmodium vivax Isolates from Thailand - Chootong, Patchanee (Parasitol Int, 2014)
Plasmodium vivax Duffy Binding Protein II (DBPII) plays an important role in reticulocyte invasion and is a potential vaccine candidate against vivax malaria. However, polymorphisms in DBPII are a challenge for the successful design of a broadly protective vaccine. In this study, the genetic diversity of DBPII among Thai isolates was analyzed from P. vivax-infected blood samples and polymorphism characters were defined with the MEGA4 program. Sequence analysis identified 12 variant residues that are common among Thai DBPII haplotypes with variant residues L333F, L424I, W437R and I503K having the highest frequency. Variant residue D384K occurs in combination with either E385K or K386N/Q. Additionally, variant residue L424I occurs in conjunction with W437R in most Thai DBPII alleles and these variants frequently occur in combination with the I503K variant. The polymorphic patterns of Thai isolates were defined into 9 haplotypes (Thai DBL-1, -2, -3, etc…). Thai DBL-2, -5, -6 haplotypes are the most common DBPII variants in Thai residents. To study the association of these Thai DBPII polymorphisms with antigenic character, the functional inhibition of anti-DBPII monoclonal antibodies against a panel of Thai DBL variants was characterized by an in vitro erythrocyte binding inhibition assay. The functional inhibition of anti-DBPII monoclonal antibodies 3C9, 2D10 and 2C6 against Thai variants was significantly different, suggesting that polymorphisms of Thai DBPII variants alter the antigenic character of the target epitopes. In contrast, anti-DBPII monoclonal antibody 2H2 inhibited all Thai DBPII variants equally well. Our results suggest that the immune efficacy of a DBPII vaccine will depend on the specificity of the anti-DBPII antibodies induced and that it is preferable to optimize responses to conserved epitopes for broadly neutralizing protection against P. vivax.